Characterisation of volatile compounds in Cilento (Italy) figs (Ficus carica L.) cv. Dottato as affected by the drying process. (29th December 2017) - Russo, Filippo; Caporaso, Nicola; Paduano, Antonello; Sacchi, Raffaele
ABSTRACT: The present paper reports on the characterisation of white figs cv. "Dottato" from Southern Italy for their volatile compounds as a function of drying treatment, i.e. natural sun-drying or oven-drying. A comparison of the volatile profile of commercial dried figs from Turkey was also reported. Forty-two volatile compounds were identified in Dottato figs by solid-phase micro extraction coupled with gas-chromatography and mass spectrometry (SPME-GC/MS), while 55 were identified in Turkish figs. Aldehydes were the main chemical class, while ethyl alcohol, isopentyl alcohol, isopentyl alcohol acetate, ethyl acetate, 3-mehtylbutanal, hexanal, and benzaldehyde were the major compounds in both fresh and dried Dottato figs. Principal Component Analysis (PCA) explained 76.5% of the observed variance, allowing discrimination between Cilento and Turkish dried figs, and even between sun-dried and oven-treated samples. Oven treatment of Dottato figs significantly affected their volatile profile, while fig pollination is also hypothesised to have an influence. Further work could be undertaken on this aspect, potentially progressing into possible molecular markers to distinguish between fig varieties.